#### Answer

The function is odd.

#### Work Step by Step

We have that $E(-x)=E(x)$ and $O(-x)=-O(x)$.
Let $\Phi=O\circ O$ Then
$$\Phi(-x)=O\circ O(-x)=O(O(-x))=O(-O(x))=-O(O(x))=-O\circ O(x)=-\Phi(x)$$
which means that the function is odd.

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

The function is odd.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.